2022
DOI: 10.21873/invivo.12981
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Postoperative Outcomes of Colorectal Cancer Patients With Chronic Renal Failure on Dialysis

Abstract: Background/Aim: Surgery for dialysis patients requires special attention because of their physical characteristics. This study aimed to investigate the shortterm postoperative outcomes of colorectal cancer patients with chronic renal failure (CRF) on dialysis and aimed to investigate safer treatment options for these patients. Patients and Methods: A total of 1,504 colorectal cancer patients who underwent primary resection between January 2008 and December 2018 were included. A retrospective analysis of clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In our study, patients with RF exhibited significant differences in postoperative complications compared to those without RF. Previous studies reported complication rates ranging from 36.8 to 50% in HD patients after CRC surgery (7,8). The postoperative complication rate (CD ≥2) was 44.4% in this study with a severe complication rate of 17.7%, and there were no patient deaths within 30 days after surgery.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…In our study, patients with RF exhibited significant differences in postoperative complications compared to those without RF. Previous studies reported complication rates ranging from 36.8 to 50% in HD patients after CRC surgery (7,8). The postoperative complication rate (CD ≥2) was 44.4% in this study with a severe complication rate of 17.7%, and there were no patient deaths within 30 days after surgery.…”
Section: Discussionsupporting
confidence: 45%
“…Most RF patients, including those undergoing HD, tend to have comorbid diseases, such as cardiovascular disease, atherosclerotic disease, metabolic disease, and diabetes mellitus (7,10). Additionally, they face many disadvantages, such as organ vulnerability, delayed healing, increased susceptibility to bleeding, and a higher risk of infection, leading to elevated perioperative complications (8).…”
Section: Discussionmentioning
confidence: 99%
“…[12] Not surprisingly, compared to nondialysis patients, these patients were less likely to undergo a laparoscopic approach. [11,13] Recently, Shiraishi et al published a retrospective study of the clinical data of 19 hemodialysis patients who underwent elective curative resection of colorectal cancer. [14] Although approximately 80% of these patients underwent minimally invasive surgery, short-term complications still occurred more frequently in these patients than in nonhemodialysis patients (36.8% vs. 15.5%, p = 0.009).…”
Section: Introductionmentioning
confidence: 99%